A COMPARATIVE STUDY ON THE FACTORS INFLUENCING THE CHOICE OF ANY PARTICULAR PHARMACY BY THE PATIENTS. - Dr. Malini S; Dr. B Jaykar; Dr. Santhosh M Mathews (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
It was across sectional prospective observational study design. The study was conducted at and around five districts, by covering rural, urban areas using validated questionnaire. The patients were included from all the areas like, Government hospitals, Primary Health Centres, Private hospitals and as well as Community Pharmacies. The factors influencing the choice of any particular Pharmacy is extensively studied. A separate question was given and the factors were critically studied. There were eight important parameters based on which it was studied. The location and accessibility to the pharmacy and opening hours were found to influence the patients very much. The availability good medicines and getting it in a competitive price were also found as a parameter to select a particular pharmacy by the patients. But the confidentiality and privacy of the prescriptions and appearance of the pharmacy were not at all a significant factor for the patients to select a particular pharmacy. The study concluded that the present pharmacy services are to be updated to practice modern concept of pharmaceutical care.